Method for preparing anhydrite-lead vitriol by curing lead with sulfate and application of anhydrite-lead vitriol
The preparation of anhydrite-lead alum series solid solution by sulfate curing method solves the problem that the existing technology is difficult to effectively seal and deal with toxic metal lead, realizes stable storage of lead and long-term stacking in the environment, and reduces the harm of lead pollution to the environment and health.
Patent Information
- Application Number
- CN202411754563.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is difficult to effectively seal and deal with toxic metal lead present in the environment, resulting in a serious threat to the environment and human health.
By sulfate curing method, lead is cured into anhydrotest-lead alum series solid solution and calcined at high temperature to form a stable lead sealant. This method prepares anhydrotest-lead alum solid solution that can effectively seal lead by adjusting the reaction of Ca/Pb molar ratio and sodium sulfate.
Effective storage of toxic metal lead is achieved, reducing the mobility and solubility of lead in soil and water bodies, reducing environmental and health hazards, and providing solutions for long-term stacking of lead and wastewater removal.
Smart Images

Figure CN119591213A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of environmental safety and technology, and relates to a method and application of preparing anhydrite-lead alum by solidifying lead with sulfate. The method solidifies lead in an aqueous solution with sulfate to obtain a series of lead-containing gypsum solid solutions, and the anhydrite-lead alum obtained by removing water molecules at high temperature can realize the sealing of toxic metal lead. Background Art
[0002] In the past few decades, due to the vigorous development of global industrialization, heavy metals have entered the atmosphere, water and soil in the form of slag, tailings or flue gas, causing various environmental pollutions, among which lead-based pollutants are particularly serious. Human activities such as agriculture and industrial product manufacturing directly or indirectly contribute a large amount of lead-based pollutants to the environment, and soil and water bodies are among the recipients. It is well known that these lead-based pollutants cause serious harm to the environment and health. Solidification technology provides an effective means to deal with lead pollution problems by significantly reducing the mobility and solubility of lead in soil and water bodies. Lead is a non-essential element for the human body. When the concentration of lead in the blood is greater than 1.2 μmol / L, it will cause lead poisoning. The symptoms are mainly headache, dizziness, constipation, abdominal pain, sore limbs, anemia, arteriosclerosis, gastrointestinal ulcers, toxic hepatitis and neurasthenia. Lead ions are very harmful to human health. Therefore, more scientific methods and means are used to deal with Pb 2+ , achieving harmlessness and resource utilization, which has become the primary issue for sustainable development of environment and health.
[0003] Anhydrite is used as a raw material for the production of Portland cement. It is often added to clinker during cement manufacturing to control the setting time and improve the strength and durability of the final product. Anhydrite helps regulate the hydration reaction in cement, thereby forming a strong and stable concrete. In recent years, experts and scholars have carried out a series of technical studies on the solidification of heavy metal-contaminated soil and water bodies by cement and other additives, and have achieved rich research results. The main modes of action of cement on heavy metals are adsorption, physical encapsulation, ion exchange and chemical precipitation. Various modes interact with each other to change the occurrence form of heavy metals to achieve a stabilization effect. Cement materials are compatible with a variety of wastes and can treat a wide range of chemical components. They can make most liquid wastes react chemically with cement, and the cement solidified body formed has good chemical and physical long-term stability, relatively good mechanical and structural properties, and relatively low permeability. The solidification mechanism of heavy metals in cement-based materials mainly includes: adsorption, formation of insoluble substances, ion or ion group substitution, and encapsulation. Adsorption can be divided into physical adsorption and chemical adsorption. Physical adsorption mainly relies on the van der Waals force between molecules or the attraction between opposite charges, so physical adsorption is often reversible; while chemical adsorption is a stronger form of adsorption connected by covalent bonds. Ion or ion group substitution refers to the process in which heavy metal ions or ion groups enter the structure of the hydration product and replace the original ions or ion groups in the structure. This process needs to meet the charge balance and ion size requirements. When heavy metals are solidified, ion substitution and chemical adsorption on the product surface often refer to the same process.
[0004] Anhydrite and lead alum are sulfates of different composition but related structures. In recent years, dissolution-reprecipitation reactions have been envisioned as an effective means of removing dissolved toxic metals from the environment by incorporating dissolved contaminants into the crystalline structure of the solid phase. The dissolution of toxic metals is significantly hindered when the new solid phase forms a continuous, uniform layer on the mineral substrate. Such a barrier is more likely to form when there is an epitaxial relationship between the newly formed phase and the mineral matrix. Both anhydrite and lead alum crystallize in the orthorhombic system, and their structure is based on alternating edge-sharing (SO4 2- ) tetrahedron and [n] - Chain of coordination polyhedra. In the anhydrite structure, Ca is located in 4 [SO4] 2- Between, and 8 O 2- Adjacent, each O 2- With 1 S 6+ and two Ca 2+ adjacent; in the lead alum structure, Pb 2+ With [SO4] 2-Form irregular coordination polyhedrons. When a lead-containing aqueous solution interacts with anhydrite (CaSO4), the dissolved lead can be removed to form lead alum. Based on this principle, anhydrite-lead alum is prepared by adjusting the different molar ratios of Ca / Pb and reacting with sodium sulfate, which can effectively fix lead. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing anhydrite-lead alum series solid solution precipitation by solidifying lead with sulfate. The prepared sulfate solid solution is calcined at high temperature, and then subjected to X-ray diffraction (XRD) and scanning electron microscope (SEM) analysis; the leaching concentrations of calcium and lead in the anhydrite-lead alum series solid solution under nitrogen degassed ultrapure water, pH=3 and pH=9 ultrapure water conditions are regularly monitored, and the distribution of calcium and lead in the solid-liquid two-phase system is experimentally analyzed, so as to provide a theoretical basis for exploring the migration and transformation of lead-containing sulfate in different environments.
[0006] A method for preparing anhydrite-lead alum series solid solution by using sulfate-solidified lead, the specific steps of which are as follows:
[0007] (1) Weigh appropriate amounts of sodium sulfate, calcium nitrate, and lead nitrate, and use ultrapure water to prepare 1.0 mol / L Na2SO4 solution, 1.0 mol / L Ca(NO3)2 solution, and 1.0 mol / L Pb(NO3)2 solution, respectively.
[0008] (2) Take several clean beakers and prepare 50 mL of mixed solutions with Ca(NO3)2 / Pb(NO3)2 molar ratios of 1.0 / 0.0, 0.9 / 0.1, 0.8 / 0.2, 0.7 / 0.3, 0.68 / 0.32, 0.66 / 0.34, 0.64 / 0.36, 0.62 / 0.38, 0.6 / 0.4, 0.5 / 0.5, 0.4 / 0.6, 0.3 / 0.7, 0.2 / 0.8, 0.1 / 0.9, 0.08 / 0.92, 0.06 / 0.94, 0.04 / 0.96, 0.02 / 0.98, and 0.0 / 1.0, respectively.
[0009] (3) Take 19 clean 1000 mL polyethylene bottles and number them according to different molar ratios; pour 500 mL of Na2SO4 solution into the mixed solution of Ca(NO3)2 and Pb(NO3)2 in five portions; start stirring at 20℃ and 500 r / min and react for 15 min.
[0010] (4) After the reaction is completed, seal the tube, age it at room temperature for 1 day, measure the pH of the supernatant, and filter it.
[0011] The sulfate-solidified lead obtained in the present invention is used to prepare anhydrite-lead alum series solid solutions for the removal of lead in wastewater and the long-term stacking of lead-containing waste residues in the environment, and the specific steps are as follows:
[0012] Solid-liquid separation is carried out at room temperature, and the obtained solid precipitate is washed with ultrapure water and alcohol. The washed solid precipitate is dried in an oven at 90°C for 24 h, and then calcined in a tubular furnace at 830°C for 20 min. This completes the preparation of anhydrite-lead alum series solid solutions and realizes the long-term storage of lead-containing waste slag in the environment.
[0013] Leaching test: Weigh 20 g of anhydrite-lead alum series solid solution and place it in 3 groups of 5L polyethylene bottles. Add 5L of N2 degassed ultrapure water, pH=3 HCl solution, and pH=9 NaOH solution to each group of bottles. Seal the PET bottles, shake them gently, and dissolve them at room temperature (air conditioning 25℃). During the dissolution process, take a certain volume of supernatant sample at 1 h, 3 h, 6 h, 12 h, 1 d, 2 d, 3 d, 5 d, 10 d, 15 d, 20 d, 30 d, 40 d, 50 d, 60 d, 70 d, 80 d, 90 d, 120 d, 150 d, 180 d, 210 d, 240 d, 270 d, and 300 d (h means hours, d means days) to determine Pb 2+ The concentration of lead is obtained by calculating the leaching concentration of lead. After 80 days of leaching, the leaching concentration of lead in the anhydrite-lead alum series solid solution is lower under the conditions of N2 degassed ultrapure water and pH=3, while it is higher under the conditions of pH=9. Therefore, when the anhydrite-lead alum series solid solution is piled up in the environment, it should be avoided in an alkaline environment to avoid lead dissolution and pollution accidents.
[0014] The present invention utilizes calcium nitrate and lead nitrate to undergo a coprecipitation reaction with sodium sulfate to obtain anhydrite-lead alum series solid solutions. The anhydrite-lead alum series solid solutions obtained by the method can effectively remove heavy metal element lead in an aqueous solution, and the lead leaching concentration is low under acidic and neutral conditions. Therefore, the present invention utilizes sulfate to solidify lead in an aqueous solution, and the anhydrite-lead alum obtained after removing water molecules at high temperature can achieve the sealing of toxic metal lead. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The XRD diagrams of the anhydrite-lead alum series solid solutions prepared in Examples 1 to 5 of the present invention, wherein the anhydrite standard card is PDF#01-086-2270, and the lead alum standard card is PDF#01-089-7356.
[0016] Figure 2This is a scanning electron microscope image (SEM) of the anhydrite-lead alum solid solution prepared in Example 1 of the present invention.
[0017] Figure 3 This is a scanning electron microscope image (SEM) of the anhydrite-lead alum solid solution prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0018] Example 1
[0019] At 20±3℃, pour 50 mL of 1.0 mol / L Ca(NO3)2 solution into a 1000 mL polyethylene bottle, place the polyethylene bottle in the middle of a magnetic stirrer, set the speed to 500 r / min, and start stirring; after a period of time, add 500 mL of 1.0 mol / L Na2SO4 solution into the polyethylene bottle every two minutes; react for a certain period of time, seal with plastic wrap and age for 1 day; separate the solid and liquid by filtration, and wash the beaker with ultrapure water 3 times and anhydrous ethanol once during the filtration process. The obtained solid sample is dried in a 90℃ forced air drying oven for 24 hours, and then calcined at 830℃ for 20 minutes in a tubular furnace to obtain anhydrite.
[0020] Example 2
[0021] At 20±3℃, 49 mL 1.0 mol / L Ca(NO3)2 solution and 1 mL 1.0 mol / L Pb(NO3)2 solution were poured into a 1000 mL polyethylene bottle, and the polyethylene bottle was placed in the middle of a magnetic stirrer, the speed was set to 500 r / min, and stirring was started; after a period of time, 500 mL 1.0 mol / L Na2SO4 solution was added to the polyethylene bottle every two minutes; after a certain reaction time, the bottle was sealed with plastic wrap and aged for 1 day; solid-liquid separation was performed by suction filtration, and during the suction filtration process, the beaker was washed 3 times with ultrapure water and 1 time with anhydrous ethanol. The obtained solid sample was dried in a 90℃ forced air drying oven for 24h, and then calcined in a tubular furnace at 830℃ for 20 min to obtain an anhydrite-lead alum solid solution with a Ca(NO3)2 / Pb(NO3)2 molar ratio of 0.90 / 0.10.
[0022] Leaching test:
[0023] After dissolving for 80 days at 25°C in nitrogen-degassed ultrapure water, the lead leaching concentration was 0.1794 mmol / L;
[0024] After dissolving in ultrapure water at 25°C and pH=3 for 80 days, the lead leaching concentration was 0.1703 mmol / L;
[0025] After dissolving in ultrapure water at 25°C and pH=9 for 80 days, the leaching concentration of lead was 0.1862 mmol / L.
[0026] Example 3
[0027] At 20±3℃, 48 mL of 1.0 mol / L Ca(NO3)2 solution and 2 mL of 1.0 mol / L Pb(NO3)2 solution were poured into a 1000 mL polyethylene bottle, and the polyethylene bottle was placed in the middle of a magnetic stirrer, and the speed was set to 500 r / min, and stirring was started; after a period of time, 500 mL of 1.0 mol / L Na2SO4 solution was added to the polyethylene bottle every two minutes; after a certain reaction time, the bottle was sealed with plastic wrap and aged for 1 day; solid-liquid separation was performed by suction filtration, and during the suction filtration process, the beaker was washed 3 times with ultrapure water and 1 time with anhydrous ethanol. The obtained solid sample was dried in a 90℃ forced air drying oven for 24h, and then calcined in a tubular furnace at 830℃ for 20 min to obtain an anhydrite-lead alum solid solution with a Ca(NO3)2 / Pb(NO3)2 molar ratio of 0.80 / 0.20.
[0028] Leaching test:
[0029] After dissolving for 80 days at 25°C in nitrogen-degassed ultrapure water, the lead leaching concentration was 0.1609 mmol / L;
[0030] After dissolving in ultrapure water at 25°C and pH=3 for 80 days, the lead leaching concentration was 0.1716 mmol / L;
[0031] After dissolving in ultrapure water at 25°C and pH=9 for 80 days, the leaching concentration of lead was 0.1824 mmol / L.
[0032] Example 4
[0033] At 20±3℃, 47 mL 1.0 mol / L Ca(NO3)2 solution and 3 mL 1.0 mol / L Pb(NO3)2 solution were poured into a 1000 mL polyethylene bottle, and the polyethylene bottle was placed in the middle of a magnetic stirrer, the speed was set to 500 r / min, and stirring was started; after a period of time, 500 mL 1.0 mol / L Na2SO4 solution was added to the polyethylene bottle every two minutes; after a certain reaction time, the bottle was sealed with plastic wrap and aged for 1 day; solid-liquid separation was performed by suction filtration, and during the suction filtration process, the beaker was washed 3 times with ultrapure water and 1 time with anhydrous ethanol. The obtained solid sample was dried in a 90℃ forced air drying oven for 24h, and then calcined in a tubular furnace at 830℃ for 20 min to obtain an anhydrite-lead alum solid solution with a Ca(NO3)2 / Pb(NO3)2 molar ratio of 0.70 / 0.30.
[0034] Leaching test:
[0035] After dissolving for 80 days at 25°C in nitrogen-degassed ultrapure water, the lead leaching concentration was 0.1529 mmol / L;
[0036] After dissolving in ultrapure water at 25°C and pH=3 for 80 days, the lead leaching concentration was 0.1593 mmol / L;
[0037] After dissolving in ultrapure water at 25°C and pH=9 for 80 days, the leaching concentration of lead was 0.1732 mmol / L.
[0038] Example 5
[0039] At 20±3℃, 46 mL of 1.0 mol / L Ca(NO3)2 solution and 4 mL of 1.0 mol / L Pb(NO3)2 solution were poured into a 1000 mL polyethylene bottle, and the polyethylene bottle was placed in the middle of a magnetic stirrer, and the speed was set to 500 r / min, and stirring was started; after a period of time, 500 mL of 1.0 mol / L Na2SO4 solution was added to the polyethylene bottle every two minutes; after a certain reaction time, the bottle was sealed with plastic wrap and aged for 1 day; solid-liquid separation was performed by suction filtration, and during the suction filtration process, the beaker was washed with ultrapure water 3 times and anhydrous ethanol once. The obtained solid sample was dried in a 90℃ forced air drying oven for 24 hours, and then calcined in a tubular furnace at 830℃ for 20 min to obtain an anhydrite-lead alum solid solution with a Ca(NO3)2 / Pb(NO3)2 molar ratio of 0.60 / 0.40.
[0040] Leaching test:
[0041] After dissolving for 80 days at 25°C in nitrogen-degassed ultrapure water, the lead leaching concentration was 0.1684 mmol / L;
[0042] After dissolving in ultrapure water at 25°C and pH=3 for 80 days, the lead leaching concentration was 0.1630 mmol / L;
[0043] After dissolving in ultrapure water at 25°C and pH=9 for 80 days, the leaching concentration of lead was 0.1744 mmol / L.
Claims
1. A method for preparing anhydrite-lead alum series solid solution by using sulfate solidified lead, the specific steps of which are: Step (1): Material preparation; the chemicals used in the experiment include sodium sulfate, calcium nitrate and lead nitrate, and the experimental water is ultrapure water produced by a Milli-Q instrument (resistivity is 18.2 MΩ*cm); Step (2): Solution preparation: Weigh appropriate amounts of reagents and use volumetric flasks to prepare 1.0 mol / L Na2SO4 solution, 1.0 mol / L Ca(NO3)2 solution, and 1.0 mol / L Pb(NO3)2 solution, respectively; then, take several clean beakers and prepare 50 mL of mixed solutions with different Ca(NO3)2 / Pb(NO3)2 molar ratios; Step (3): Reaction process; Take 19 clean 1000 mL polyethylene bottles and number them according to different molar ratios; Pour 500 mL of Na2SO4 solution into the mixed solution of Ca(NO3)2 and Pb(NO3)2 in 5 times, with an interval of 1 minute between each addition. During this process, a glass rod needs to be used for drainage to prevent the reaction solution from splashing; Stir at 20°C and 500 r / min and react for 15 min; Step (4): Aging and sampling: After the reaction is completed, seal the container, age it at room temperature for 1 day, measure the pH of the supernatant, and filter to obtain the solid phase; Step (5): Drying and calcining: The obtained solid precipitate is washed with ultrapure water and alcohol for 3 to 5 times, and the washed solid precipitate is dried in an oven at 90°C for 24 h, and then calcined in a tubular furnace at 830°C for 20 min to obtain the target anhydrite-lead alum series solid solution.
2. An application of the sulfate-solidified lead prepared by the method of claim 1 to prepare anhydrite-lead alum series solid solutions, characterized in that It can be used to remove lead from wastewater and to store lead-containing waste residues in the environment for a long time. Its characteristics are: The leaching test of anhydrite-lead alum series solid solution prepared by sulfate solidification lead in N2 degassed ultrapure water, pH=3 HCl solution, and pH=9 NaOH solution showed that after 80 days of leaching, the leaching concentration was only 0.1529 mmol / L~0.1744 mmol / L under the condition of pH=3~9.
Citation Information
Patent Citations
Sodium arsenic alunite solid solution and preparation method thereof and application of preparation method
CN104355374A
Material and method for treating lead-containing wastewater
CN105776366A
Lead-containing raw material wet recovery treatment method
CN107641714A
Preparation method and application of calcite-cerusite solid solution
CN114804192A
Resourceful treatment method of iron-containing raw material
CN116904747A